2021
DOI: 10.3390/vaccines9111325
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 on Anti-S Antibody Response in Healthcare Workers Six Months Post-Vaccination

Abstract: The current study aimed to determine to what extent prior COVID-19 infection affects the response of specific antibodies following vaccination. The study involved 173 healthcare professionals who completed the two-dose vaccination course with BNT162b2, including 40 who previously experienced clinical COVID-19. The levels of anti-SARS-CoV-2 S1S2 IgG (anti-S) and, in some cases, anti-SARS-CoV-S-RBD IgG (anti-S-RBD) were determined six months after complete vaccination. A level exceeding the cut-off values for bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 13 publications
6
6
0
Order By: Relevance
“…One dose of vaccine received after COVID-19 is sufficient to produce peak antibody levels extremely quickly. These findings agree with the results of previous studies and go in line with the recommendation of second dose administration 6 months after recovering from COVID-19 [14][15][16][17][18][19][20][21][22][23][24][25][27][28][29][30]. Furthermore, these results can be explained by the limited humoral response to SARS-CoV-2 and the self-maintenance nature of the immune system.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…One dose of vaccine received after COVID-19 is sufficient to produce peak antibody levels extremely quickly. These findings agree with the results of previous studies and go in line with the recommendation of second dose administration 6 months after recovering from COVID-19 [14][15][16][17][18][19][20][21][22][23][24][25][27][28][29][30]. Furthermore, these results can be explained by the limited humoral response to SARS-CoV-2 and the self-maintenance nature of the immune system.…”
Section: Discussionsupporting
confidence: 92%
“…While IgG antibodies can be detected in a vast majority of COVID-19 patients 10 days after the infection, their levels generally decrease over time [4][5][6][7]. Similar patterns in antibody dynamics could be predicted after vaccination [15][16][17][18][19][20][21]. Post-COVID-19 specific antibodies are directed toward different antigens, such as the nucleoprotein (NP) and spike (S) antigens.…”
Section: Introductionmentioning
confidence: 99%
“…In Finland, mRNA vaccine displayed only 53% from the initial IgG level after 6 months, but antibody waning was not observed against COVID-19 hospitalization 28 . In a HCW Polish cohort it was reported that there are higher levels of specific antibodies 6 months after vaccination in subjects experiencing the disease after the first round of vaccination, the finding supporting once more the use of a booster dose, especially for non-infected subjects 29 .…”
Section: Introductionmentioning
confidence: 91%
“…In a cohort analysis of SARS-CoV-2 anti-S-RBD IgG levels and neutralizing antibodies in fully vaccinated healthcare workers, the concentration of anti-RBD and anti-S antibodies was increased in individuals who received the full dose of Pfizer/BioNTech vaccine [19] . A study involving healthcare professionals who received two doses of BNT162b2 vaccine showed increased levels of anti-SARS-CoV-2 S1S2 IgG and anti-SARS-CoV-2 S-RBD IgG at 6 months after vaccination [20] . Firinu et al.…”
Section: Discussionmentioning
confidence: 99%